2018
DOI: 10.3310/phr06020
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative case management to aid return to work after long-term sickness absence: a pilot randomised controlled trial

Abstract: BackgroundDespite high levels of employment among working-age adults in the UK, there is still a significant minority who are off work with ill health at any one time (so-called ‘sickness absence’). Long-term sickness absence results in significant costs to the individual, to the employer and to wider society.ObjectiveThe overall objective of the intervention was to improve employee well-being with a view to aiding return to work. To meet this aim, a collaborative case management intervention was adapted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…Other studies testing enhanced occupational support have used alternative methods to identify and target sick-listed staff, such as screening routine sickness absence reporting systems followed by direct mail invitations. 23 Although in Kenning et al's study 23 it was noted that identifying prospective participants via this method had generated a smaller than expected number of participants, the overall proportion of eligible sick-listed staff who were screened and consented into their study was larger than in the current study. Furthermore, it is envisaged that adopting a similar method in a future main study will vastly increase the number of prospective participants being screened for eligibility.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Other studies testing enhanced occupational support have used alternative methods to identify and target sick-listed staff, such as screening routine sickness absence reporting systems followed by direct mail invitations. 23 Although in Kenning et al's study 23 it was noted that identifying prospective participants via this method had generated a smaller than expected number of participants, the overall proportion of eligible sick-listed staff who were screened and consented into their study was larger than in the current study. Furthermore, it is envisaged that adopting a similar method in a future main study will vastly increase the number of prospective participants being screened for eligibility.…”
Section: Discussionmentioning
confidence: 54%
“…This reflected similar observations in the previous CAMEOS (CAse Management to Enhance Occupational Support) trial. 23 Furthermore, we found that the proportion of sick-listed staff with a CMD who were referred to OH within 8-28 days was smaller than the proportion reported by the OH providers who participated in the survey of care as usual.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations